Diagnostic Accuracy of X-Ray PNS for Paranasal Sinuses (X-Ray PNS) Sinus Pathologies with Computed Tomography Paranasal Sinuses (CT PNS) A The Gold Standard - Israr, Karishma; Wasif Farman; Siddique Umer, Ummara; Abdullah Safi; Shahjehan Alam; Hadia Abid (Journal of Gandhara Medical and Dental Science, 2024)
OBJECTIVES To determine the diagnostic accuracy of X-ray PNS in different pathologies of paranasal sinuses, using CT PNS as the gold standard, and establishing X-ray PNS as a potential first-line screening tool. METHODOLOGY This cross-sectional study was conducted over two years in the Department of Radiology, Rehman Medical Institute Peshawar. 100 patients in the sample with suspected PNS pathologies were selected through the purposive sampling technique, aged 18-70. All patients underwent X-ray PNS initially, followed by CT scans. CT PNS was performed even in cases with normal X-ray findings to check for false negatives or positives. RESULTS Out of 100 patients, 56% were male. Most PNS pathologies (55%) were in the 15-35 age group (mean age 24 years, SD ±3.89). The most common symptoms were nasal obstruction (40%) and headache (39%). X-ray PNS showed 67% sensitivity, 60% specificity, 85% PPV, and 64% NPV. The overall diagnostic accuracy of X-ray PNS was 66% compared to CT PNS. CONCLUSION X-ray PNS demonstrates a diagnostic accuracy of 66% in diagnosing PNS pathologies. While not as comprehensive as CBCT, X-ray PNS shows potential as a first-line screening tool, particularly for larger sinuses, potentially reducing unnecessary radiation exposure from CT scans.